HIV Testing : Principles and Practice - Gersovitz, Mark (World Bank, 2013)
Testing is a potentially important intervention to slow the HIV epidemic in Africa and elsewhere. Some countries in Africa have achieved high levels of testing but most have not. Cost, price, and questions of confidentiality have limited the expansion of testing. It looks possible, however, that there are choices as to the design of testing programs that would expand the number of people who could know their HIV status in ways that would be worthwhile.